From Historic Knowledge to School Knowledge. Teacher Planning for the Teaching of History and Social Sciences (2019)
Historic knowledge is confronted with the challenge of becoming school knowledge. This process begins with curricular decisions taken by the Ministry of Education on educational contents and is consolidated in the school classroom through the teachers ́ professional decisions. In this context, this paper discusses planning processes for the subject of History, by pre-service teachers in their practicum and new teachers of a public, regional Chilean university. This case study examines the teaching of social concepts in these two groups, by means of interviews, class observation, and document analysis. Some research conclusions are: that planning processes are directly related to the conceptual and disciplinary knowledge of the teacher, that there is relative autonomy in planning processes mainly due to the context, and that methodological and external limitations are identified in both groups. The presence of the social concepts in planning processes is primarily implicit, prioritizing events over conceptual revisions.